2002
DOI: 10.1016/s0893-133x(02)00362-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rapid Tryptophan Depletion on Sleep Electroencephalogram and Mood in Subjects with Partially Remitted Depression on Bupropion

Abstract: Serotonin has been implicated in both sleep and mood regulation. When central serotonin was depleted with a tryptophan-free amino acid drink (TFD),Serotonin (5-hydroxytryptamine; 5-HT) has long been implicated in the pathophysiology of depression as well as in the sleep and mood abnormalities associated with depression (Maes and Meltzer 1995). Specifically, deficiencies in 5-HT levels or in cellular responses to 5-HT neurotransmission are thought to be involved in depression. In support of this idea, deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
3
14
0
2
Order By: Relevance
“…In line with this, Cryan et al (2001Cryan et al ( , 2004 reported that the antidepressant-like effect of bupropion is primarily attributable to the NE system. Furthermore, although tryptophan depletion did not induce relapses in bupropion-remitted patients with depression, certain mood measures were decreased (Evans et al 2002). The time-dependent enhancement of 5-HT and NE transmission due to reduced responsiveness of terminal α 2 -adrenergic hetero-and autoreceptors, respectively, may contribute to the therapeutic action of bupropion in major depression.…”
Section: -Htmentioning
confidence: 91%
“…In line with this, Cryan et al (2001Cryan et al ( , 2004 reported that the antidepressant-like effect of bupropion is primarily attributable to the NE system. Furthermore, although tryptophan depletion did not induce relapses in bupropion-remitted patients with depression, certain mood measures were decreased (Evans et al 2002). The time-dependent enhancement of 5-HT and NE transmission due to reduced responsiveness of terminal α 2 -adrenergic hetero-and autoreceptors, respectively, may contribute to the therapeutic action of bupropion in major depression.…”
Section: -Htmentioning
confidence: 91%
“…13,61,71,72,79,85,98,118,119,123,124 Six studies included patients ( < 25% of total) with Bipolar I or II disorder. 15,98,99,108,117,124 In total, this were 14 patients. The reason that several apparently high-quality studies were rated as moderate in this review was due to the lack of presentation of the mood effects, which in those studies was not the primary outcome.…”
Section: Identified Studiesmentioning
confidence: 99%
“…In remitted patients using AD decreased mood after ATD was especially seen in the first 5 months after the achievement of remission (pooled Hedges' g À0.55 (À0.90 to À0.21) Q res = 47.18, df = 2, P < 0.0001). 92,95,[99][100][101]105 In contrast, remitted patients without AD showed more decrease in mood after X2 months of remission (Hedges' g À1.65 (À2.60 to À0.69) Q res = 13.81, df = 2, P = 0.001) 67,92,93 (figure available on request).…”
Section: Atdmentioning
confidence: 99%
See 1 more Smart Citation
“…ATD has been shown to reduce concentrations of 5-HT in the cerebrospinal fluid (CSF) of animals (Moja et al 1989) and humans (Carpenter et al 1998;Williams et al 1999), with a maximal decrease in plasma tryptophan 5-7 h after intake of the amino acid mixture (Rubia et al 2005). ATD has been shown to have clear effects on several sleep parameters, especially REM sleep (Haynes et al 2004;Moore et al 1998;Evans et al 2002;Landolt et al 2003;Bhatti et al 1998;Riemann et al 2002;Voderholzer et al 1998).…”
Section: Introductionmentioning
confidence: 99%